2020
DOI: 10.1016/j.healun.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

International Society for Heart and Lung Transplantation consensus statement for the standardization of bronchoalveolar lavage in lung transplantation

Abstract: Bronchoalveolar lavage (BAL) is a key clinical and research tool in lung transplantation (LTx). However, BAL collection and processing are not standardized across LTx centers. This International Society for Heart and Lung Transplantation–supported consensus document on BAL standardization aims to clarify definitions and propose common approaches to improve clinical and research practice standards. The following 9 areas are covered: (1) bronchoscopy procedure and BAL collection, (2) sample handling, (3) sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 116 publications
(192 reference statements)
0
41
1
Order By: Relevance
“…Despite the fact that no single clinically useful biomarker has been identified yet, several interesting markers have been linked to CLAD development in BAL, blood and lung tissue. Todd et al recently identified upregulation of amphiregulin, an epidermal growth factor receptor (EGFR) ligand with putative role in airway injury and repair regulation, in BAL fluid of CLAD patients (20). In situ hybridization of CLAD tissue identified abundant EGFR and amphiregulin transcript expression in the airway epithelial cells of fibrotic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that no single clinically useful biomarker has been identified yet, several interesting markers have been linked to CLAD development in BAL, blood and lung tissue. Todd et al recently identified upregulation of amphiregulin, an epidermal growth factor receptor (EGFR) ligand with putative role in airway injury and repair regulation, in BAL fluid of CLAD patients (20). In situ hybridization of CLAD tissue identified abundant EGFR and amphiregulin transcript expression in the airway epithelial cells of fibrotic regions.…”
Section: Discussionmentioning
confidence: 99%
“…The demographic characteristics of the study participants are provided in Table 1. BAL sample collection: Patients underwent bronchoscopy for surveillance or for diagnosis of ALAD. BAL was obtained according to a standard protocol in accordance with international guidelines (2). Two 50 mL-aliquots of saline were instilled with the bronchoscope in a wedged position in either the right middle lobe or lingula.…”
Section: Methodsmentioning
confidence: 99%
“…Lung transplantation (LT) is a life-saving treatment option for advanced lung diseases ( 1 ). However, long-term survival after LT remains significantly lower than after transplantation of other solid organs, despite a substantial improvement in recent years ( 2 ). The main factor limiting long-term survival is chronic lung allograft dysfunction (CLAD), a progressive fibrotic process that destroys the lung allograft and is driven by inflammation and alloimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up bronchoscopies after treatment of ACR to confirm resolution is performed by 72.4% of centers. 116…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…A recent ISHLT consensus document provides recommendations for BAL standardization collection and processing and is expected to facilitate improvement and development of BAL-based diagnostics. 116 BAL cellular components: several studies have shown increased BAL cellularity and also increases leukocyte subtypes during ACR, although the findings are not sufficiently specific to allow diagnosis. [131][132][133][134][135] Interestingly, BAL cell immunophenotyping may discriminate between infection and acute rejection with CD25 þ cell, natural killer cell, monocyte, lymphocyte, and eosinophil percentages correlating with ACR.…”
Section: Promising Less-invasive Diagnostic Toolsmentioning
confidence: 99%